The Effects of Exchange Rate Changes on Trade Balance in Sudan - Ibrahim Ahmed, Ahmed Abd Allah (2001)
One of the primary economic objectives of most developing countries is to improve their trade balance. Economists have suggested that trade deficit can be reduced through currency devaluation. This study attempts to determine the effects of devaluation on the trade balance of Sudan and the pass-through effects on Sudan's major export prices by employing Vector Error Correction Model (VECM). The results from the study suggest that the elasticities of import demand with respect to the price ratio of imports relative to domestic price and domestic income are high, while that of the real effective exchange rate is low. The elasticities of export demand with respect to price ratio of exports relative to foreign price, foreign income and real effective exchange rate are high. In particular, the export demand for cotton and gum arabic are elastic with respect to the exchange rate and the foreign price. For the trade balance, it is found that the elasticities of trade balance with respect to domestic income, foreign income and real effective exchange rate are all elastic. The sum of the long-run elasticities of demand of exports and imports with respect to their respective prices is greater than one and therefore the Marshall-Lerner condition is satisfied suggesting that devaluation could be a useful policy to improve the balance of payments. The findings of the study also indicate that there is a significant long-run relationship between the real effective exchange rate and trade balance indicating that devaluation could improve the trade balance in the long-run. The results of pass-through of the export prices of cotton is complete suggesting that Sudan is likely to be a price-taker in international market and therefore. devaluation of Sudanese pound will increase the demand for the export of cotton in the long-run. The pass-through for gum arabic is incomplete suggesting that Sudan is likely to be a price-maker in international market and the devaluation of the Sudanese pound may have little impact on the export demand for gum arabic in the long-run.